Improvement of L(+)-lactic acid production from cassava wastewater by Lactobacillus rhamnosus B 103 - Coelho, Luciana Fontes [UNESP]; Bolner de Lima, Cristian J. [UNESP]; Bernardo, Marcela Piassi [UNESP]; Michelena Alvarez, Georgina; Contiero, Jonas [UNESP] (Wiley-Blackwell, 2010)
BACKGROUND: L(+)-Lactic acid is used in the pharmaceutical, textile and food industries as well as in the synthesis of biodegradable plastics. The aim of this study was to investigate the effects of different medium components added in cassava wastewater for the production of L(+)-lactic acid by Lactobacillus rhamnosus B 103.RESULTS: The use of cassava wastewater (50 g L-1 of reducing sugar) with Tween 80 and corn steep liquor, at concentrations (v/v) of 1.27 mL L-1 and 65.4 mL L-1 respectively led to a lactic acid concentration of 41.65 g L-1 after 48 h of fermentation. The maximum lactic acid concentration produced in the reactor after 36 h of fermentation was 39.00 g L-1 using the same medium, but the pH was controlled by addition of 10 mol L-1 NaOH.CONCLUSION: The use of cassava wastewater for cultivation of L. rhamnosus is feasible, with a considerable production of lactic acid. Furthermore, it is an innovative proposal, as no references were found in the scientific literature on the use of this substrate for lactic acid production. (C) 2010 Society of Chemical Industry
Keywords: cassava wastewater; corn steep liquor; response surface methodology